2017
DOI: 10.3758/s13428-017-0959-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of propensity to trust and perceptions of trustworthiness on trust behaviors in dyads

Abstract: Research on trust has burgeoned in the last few decades. Despite the growing interest in trust, little is known about trusting behaviors in non-dichotomous trust games. The current study explored propensity to trust, trustworthiness, and trust behaviors in a new computer-mediated trust relevant task. We used multivariate multilevel survival analysis (MMSA) to analyze behaviors across time. Results indicated propensity to trust did not influence trust behaviors. However, trustworthiness perceptions influenced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 45 publications
(84 reference statements)
0
49
1
Order By: Relevance
“…The task is called Checkmate (Alarcon et al, 2017). It is a computer game played between two players.…”
Section: Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…The task is called Checkmate (Alarcon et al, 2017). It is a computer game played between two players.…”
Section: Taskmentioning
confidence: 99%
“…Typically, Checkmate (Alarcon et al, 2017) is played between two people, one is the banker and the other is the runner. For this study, the participant was always the banker and the runner was always a Nao robot (see Appendix C).…”
Section: Manipulationsmentioning
confidence: 99%
“…Researchers have found that personality influences the cognitive responses to stressors [27]. Personality also influences the formation of trust perceptions [22,28]. Specifically, personality influences initial perceptions of others, but as participants have more interaction with a referent, personality plays less of a role.…”
Section: Personalitymentioning
confidence: 99%
“…Specifically, people higher in propensity to trust are more likely to trust automation in experimental [30] and real-world settings [14]. However, propensity to trust is less contextually influential as the trustor becomes more familiar with the referent [12,28]. It remains to be seen if propensity to trust influences the decision-making process after controlling for perceptions of the code (i.e., the manipulations mentioned above).…”
Section: Personalitymentioning
confidence: 99%
“…Similarly, interacting with a cooperative trustee or information about the good character of the trustee fosters trusting behaviors (Delgado et al 2005;King-Casas et al 2005), while having learnt that the other is likely to betray reduces an individual's willingness to trust Houser 2012, 2013). Importantly, previous work has shown that individuals use and integrate these sources of information to improve their trust decisions independently of individual differences in prosocial tendencies, general intelligence, or central executive abilities (Alarcon et al 2017;Bonnefon et al 2013;Chang et al 2010).…”
Section: Introductionmentioning
confidence: 99%